Evaluating The Performance Of The Faculty Of Economics In Tishreen University Using The Data Enclosure Analysis (DEA) Method. - طالب أحمد; إبراهيم السليمان (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed at the following: evaluating the performance of Syrian universities through a case study of the Faculty of Economics at Tishreen University, using the method of encircling data in the process of evaluating performance, studying and analyzing the performance of the Faculty of Economics at Tishreen University and determining its strengths and weaknesses with the possibility of providing solutions to overcome weaknesses, analyzing performance variables represented in the educational and administrative dimensions in addition to the performance dimension represented in the number of graduates and during the time period (2013-2020), Among the results obtained: - There is a statistically significant effect of the administrative dimension indicator on the performance of the Faculty of Economics - There is a statistically significant effect of the educational dimension indicator on the performance of the Faculty of Economics - We can evaluate the performance of the Faculty of Economics at Tishreen University using the data enclosure method and generalize this to other higher education institutions.